DEVELOPMENT STRATEGIES OF SMALL MEDIUM MICRO ENTERPRISES (SMEs) LOW-INTEREST LOANS - ., Zakiatuzzahrah (AdBispreneur, 2016)
ABSTRACT  The presence of SMEs not only in order to increase revenue but also to ensure equal distribution of income. This is understandable because the SMEs sector involves a lot of people with a variety of business  cases.  The  government  expects  an  independent  and  resilient  SMEs  can  flourish  and encourage  regional  and  national  economy.  Support  for  SMEs  must  of  course  be  immediately supported by the easiness for SMEs in obtaining venture capital. With the SMEs loans will increase the pace of the economy, which in turn will increase the prosperity and welfare. Keywords : strategy, development, UMKM, bank credit.   STRATEGI PENGEMBANGAN USAHA UMKM MELALUI KREDIT BUNGA RENDAH ABSTRAK  Kehadiran UKM bukan saja dalam rangka peningkatan pendapatan tapi juga dalam rangka pemerataan pendapatan. Hal ini bisa dimengerti karena sektor UKM melibatkan banyak orang dengan beragam usaha. Pemerintah mengharapkan UMKM yang mandiri, tangguh dapat berkembang, mendorong perekonomian regional serta nasional. Dukungan terhadap UMKM ini tentunya harus segera diwujudkan dengan cara memberi kemudahan-kemudahan bagi UMKM dalam mendapatkan modal usaha. Dengan adanya kredit UKM akan meningkatkan laju perekonomian, sehingga pada akhirnya akan meningkatkan kemakmuran dan kesejahteraan rakyat. Kata kunci : strategi, UMKM, kredit perbankan.